Emotion Regulation Strategies and Stress in Irish College Students and Chinese International College Students in Ireland - Sun, Yuning; Nolan, Conor (Journal of International Students, 2021)
Little is known about the association between emotion regulation strategies and perceived stress in college students, and in particular the strategies used by international students. Present research examined if differences exist in the use of emotion regulation strategies between Irish college students and Chinese international students, and investigated the relationship between emotion regulation strategies and perceived stress in these two student populations. Chinese students reported more frequent use of cognitive reappraisal and expressive suppression compared to Irish students. There was a significant negative association between the habitual use of cognitive reappraisal and levels of stress in both Irish and Chinese students. There was a significant positive relationship between the habitual use of expressive suppression and levels of stress in Irish college students, but not in Chinese students. The findings highlight the importance of cultural context when investigating the association between emotion regulation strategies and perceived stress in students.